2021
DOI: 10.1108/edi-11-2020-0324
|View full text |Cite
|
Sign up to set email alerts
|

Workplace romance and sexual favoritism in the #MeToo workplace: legal and practical considerations for management

Abstract: PurposeThe advent of the #MeToo movement has brought forth increased national and global attention to sexual assault, abuse, misconduct, discrimination and harassment in the workplace, especially by prominent executives against subordinate female employees. Accordingly, in this article, we are thoroughly analyzing one aspect of office romance and sexual conduct in the workplace, mainly sexual favoritism in the era of the #MeToo movement.Design/methodology/approachThis is a legal and case-based human resource p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Furthermore, Cavico and Mujtaba (2021) discuss how requiring those entering a WR, must disclose the relationship to human resources and sign a contract stating the relationship is consensual; can be done for some companies as a way to avoid legal problems when it comes to the possibility of a sexual harassment claim (p. 675). As the employer being proactive and setting fair workplace romance policies, will create appropriate relationship standards and conduct for the couple and coworkers.…”
Section: Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Cavico and Mujtaba (2021) discuss how requiring those entering a WR, must disclose the relationship to human resources and sign a contract stating the relationship is consensual; can be done for some companies as a way to avoid legal problems when it comes to the possibility of a sexual harassment claim (p. 675). As the employer being proactive and setting fair workplace romance policies, will create appropriate relationship standards and conduct for the couple and coworkers.…”
Section: Policymentioning
confidence: 99%
“…As the employer being proactive and setting fair workplace romance policies, will create appropriate relationship standards and conduct for the couple and coworkers. Despite the importance of workplace romance policies, it was reported by Morgan (2010, as cited in Cavico & Mujtaba, 2021) that only 13 percent of 600 companies surveyed had a formal written policy about WR, though 14 percent stated to have an "unwritten" policy (p. 679). As the years go by, it appears than more companies are increasing with the notion of written policies, as Leong (2019, as cited in Cavico & Mujtaba, 2021) reported in 2013 that 36 percent of companies had a written policy and 6 percent had a verbal policy (p. 679).…”
Section: Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the data are readily available and it is huge. It is more and more noticeable from the literature that organizations that embrace SNI can potentially add an extra layer of efficiency to the process (Breaugh, 2013;Broughton et al, 2013;Cavico et al, 2013;Heidemann et al, 2012;Caers and Castelyns, 2011;Madia, 2011). Particularly, for conducting PBC, SNSs can aid by providing readymade information already available for the employers to screen job candidates.…”
Section: Perceived Benefit (Pb)mentioning
confidence: 99%
“…Scholars in the realm of workplace relationships argue that workplace romance induces both positive and negative outcomes (Khan et al , 2017). For instance, a wide stream of studies identified different facets of work-related behaviors and attitudes such as sexual favoritism (Cavico and Mujtaba, 2021), organizational settings and politics (Sidhu et al , 2020); turnover intentions (Chory and Hoke, 2019), performance (Jung and Yoon, 2020; Khan et al , 2018); and career reputation effects (Chory et al , 2022), among others. No research, however, has investigated workplace romance as an interpersonal antecedent that might inflame workplace ostracism.…”
Section: Introductionmentioning
confidence: 99%